Consensus Decisions and Similarity Measures in International Organizations. Issue 3 (26th May 2016) - Häge, Frank; Hug, Simon
ABSTRACT: Voting behavior in international organizations, most notably in the United Nations General Assembly (UNGA), is often used to infer the similarity of foreign policy preferences of member states. Most of these measures ignore, however, that particular covoting patterns may appear simply by chance (Häge 2011) and that these patterns of agreement (or the absence thereof) are only observable if decisions are reached through roll-call votes. As the relative frequency of roll-call votes changes considerably over time in most international organizations, currently used similarity and affinity measures offer a misleading picture. Based on a complete data set of UNGA resolution decisions, we demonstrate how taking different forms of chance agreement and the relative prevalence of consensus decisions into account affects conclusions about the effect of the similarity of member states' foreign policy positions on foreign aid allocation.